POWs of the Japanese: Race and Trauma in Australia, 1970–2005. (August 2014) - Twomey, Christina
<x content-type="archive" xml:space="preserve">Abstract</x> Australian prisoners of war (POWs) captured by the Japanese in the Second World War are central figures in Australian memory of that war. A resurgence of cultural interest in their experiences began in the 1970s. This occurred within the context of three developments: the ending of the White Australia Policy, defeat in Vietnam, and the creation of the psychiatric category of post-traumatic stress disorder. In the 1970s, POWs often became a metaphor for Australia's relations with the Asian region, thereby underscoring the racial dimensions of their experience, whereas by the 1980s and into the 1990s they were prominent as the traumatized survivors of an earlier war. The article argues for the need to historicize the influence of trauma as a way of understanding the war experiences of POWs.